Morphological characteristics of regeneration of the lower jaw bone in an experiment using natural collagen with lincomycin - I.V. Chelpanova (Medičnì Perspektivi)
This study aimed to investigate the dynamic changes in the histomorphological architecture of bone-ceramic regeneration following the transplantation of natural collagen combined with lincomycin into an experimental defect of the rabbit mandible. 45 adult male rabbits aged 6-7 months and weighing 2.5-3 kg were used for the study. 20 animals were in control group and 20 animals in experimental. An additional 5 intact animals were used to study the normal structure of bone tissue in the studied area of the lower jaw. The control group consisted of animals with a bone defect that healed under a blood clot. The experimental group consisted of rabbits with the bone defect filled with natural collagen, with simultaneous intramuscular injections of lincomycin at a dose of 12 mg/kg body weight once a day for 6 days (Col-C-lincomycin). Post-traumatic bone tissue status within the defect area was monitored for 84 days. Ultrastructural changes were studied using scanning electron microscopy. To determine changes in the composition in the bone regeneration, three parameters were calculated – the relative volume of: 1) bone tissue, 2) osteoplastic material and 3) connective tissue in the bone regeneration. The data were analyzed using the Student's t-test, and a difference at p<0.05 was considered statistically significant. The research of the surface topography of the experimental bone defect in the rabbit mandible, following the implantation of Col-C material in combination with lincomycin, revealed numerous regenerative changes that occurred after injury and correlated with the dynamic changes in the relative volume of bone tissue, osteoplastic material, and connective tissue within the regeneration. Morphometric analysis of the relative volume of the constituent components of the regeneration in the experimental defect revealed a phased nature of the dynamics of the observed changes. The osteocyte lacuno-canalicular system that formed after material implantation acquired characteristics of typical structure. Foci of incomplete osteogenesis were not visualized. Unlike the control group, after the application of Col-C material in combination with lincomycin, the majority of osteons in the regeneration near the outer bone plate did not differ from the typical structure of the maternal bone in terms of both its structure and geometry.